Spatial Function Diversity in Kampung Sangkrah, Surakarta City - Musiyam, Muhammad (Universitas Muhammadiyah Surakarta, 1999)
The objective of this article is to understand the variety of space functions and the values underlying them, in kampung Sangkrah, Surakarta municipality. The study uses the inductive analysis based on the naturalistic method research. The result of the research shows that space in the kampung Sangkrah is multifunctional. The multifunction of space is resulted from the dialetical relationship between the relatively strong social relations and the limited space available to aommodate the various ativities of the kampung inhabitants. This dialetical relationship creates common norms called space tolerance, which the result in the variety of space function.